Urban environmental sustainability in colombia (2010)
This article presents the Colombia’s General Controller Office appraisal results on National urban environmental sustainability policy, implemented by metropolitan and district areas. The assessment was carried out based on several urban environmental sustainability models. The first step was the analysis of the legal framework and the design of a survey to collect information from relevant institutions at national and subnational levels: Corporaciones Autónomas Regionales (CAR), urban environmental authorities, districts and municipalities. Once the information was collected and analyzed, an indicator battery was constructed. The results showed that there is no common objective between institutions about the criteria to implement land use policies at different territorial level and scales. Additionally, there are several transport and mobility problems as well as air pollution. Based on all of these problems, we concluded that the Colombian urban areas are not sustainable.